Proteomic Identification and Quantification of Secretory Proteins in Human Dermal Fibroblast-Conditioned Medium for Wound Repair and Hair Regeneration - Suh SB; Ahn KJ; Kim EJ; Suh JY; Cho SB (Dove Medical Press, 2023)
Sang Bum Suh,1,* Keun Jae Ahn,2,* Eun Jeong Kim,1 Ji Youn Suh,1 Sung Bin Cho3 1BNV Biolab, Seoul, Korea; 2Department of Science Education, Jeju National University, Jeju, Korea; 3Yonsei Seran Dermatology and Laser Clinic, Seoul, Korea*These authors contributed equally to this workCorrespondence: Sung Bin Cho, Yonsei Seran Dermatology and Laser Clinic, 224 Siheung-daero, Seoul, 08628, Korea, Tel +82 2-2135-1375, Fax +82 70-8250-1375, Email drsbcho@gmail.comBackground: Human dermal fibroblasts secrete numerous growth factors and proteins that have been suggested to promote wound repair and hair regeneration.Methods: Human dermal fibroblast-conditioned medium (DFCM) was prepared, and proteomic analysis was performed. Secretory proteins in DFCM were identified using 1-dimensional sodium dodecyl sulphate-polyacrylamide gel electrophoresis, in-gel trypsin protein digestion, and quantitative liquid chromatography tandem mass spectrometry (LC-MS/MS). Identified proteins were analyzed using bioinformatic methods for the classification and evaluation of protein-protein interactions.Results: Using LC-MS/MS, 337 proteins were identified in DFCM. Among them, 160 proteins were associated with wound repair, and 57 proteins were associated with hair regeneration. Protein-protein interaction network analysis of 160 DFCM proteins for wound repair at the highest confidence score (0.9) revealed that 110 proteins were grouped into seven distinctive interaction networks. Additionally, protein-protein interaction network analysis of 57 proteins for hair regeneration at the highest confidence score revealed that 29 proteins were grouped into five distinctive interaction networks. The identified DFCM proteins were associated with several pathways for wound repair and hair regeneration, including epidermal growth factor receptor, fibroblast growth factor, integrin, Wnt, cadherin, and transforming growth factor-β signaling pathways.Conclusion: DFCM contains numerous secretory proteins that comprise groups of protein-protein interaction networks that regulate wound repair and hair regeneration.Keywords: human dermal fibroblast, dermal fibroblast-conditioned media, proteomic analysis, secretory protein, wound repair, hair regeneration